The process of parenting - Brooks, Jane B. (McGraw-Hill, 2004)
A comprehensive introduction to parenting that describes the many ways parents and caregivers can translate their love and concern for children into effective parenting behavior. It emphasises on the developmental process and on the changing nature of parent-children relationships, presenting a wide range of theories and research